An insect ecosystem engineer alleviates drought stress in plants without increasing plant susceptibility to an above‐ground herbivore. (19th November 2015) - Johnson, Scott N.; Lopaticki, Goran; Barnett, Kirk; Facey, Sarah L.; Powell, Jeff R.; Hartley, Susan E.
Summary: Climate change models predict more extreme rainfall patterns, ranging from droughts to deluges, which will inevitably affect primary productivity in many terrestrial ecosystems. Insects within the ecosystem, living above‐ and below‐ground, may modify plant responses to water stress. For example, some functional groups improve soil conditions via resource provision, potentially alleviating water stress. Enhanced resource provision may, however, render plants more susceptible to herbivores and negate beneficial effects. Using a model system, we tested how plants ( Brassica oleracea ) responded to drought, ambient and increased precipitation scenarios when interacting with both a soil conditioning ecosystem engineer (dung beetles; Bubas bison ) and an above‐ground herbivore, the major crop pest diamondback moth ( Plutella xylostella ). Dung beetles enhanced soil water retention by 10% and promoted growth in plants subjected to drought by 280%, relieving the impacts of water stress on plants. Under drought conditions, plants grown with dung beetles had c. 30% more leaves and were over twice as tall as those without dung beetles. Dung beetles produced a 2·7‐fold increase in nitrogen content and more than a threefold increase in carbon content of the shoots, though shoot concentrations of nitrogen and carbon were unchanged. Carbon concentrations in roots, however, were increased by dung beetles under both ambient and increased precipitation regimes. Increased precipitation reduced root and shoot nitrogen concentrations by 16% and 30%, relative to plants under ambient regimes, respectively, most likely due to dilution effects of increased plant growth under increased precipitation. Soil carbon and nitrogen concentrations were largely unaffected. While dung beetles enhanced plant growth and nitrogen content in plants experiencing drought, the anticipated increase in plant suitability to herbivores did not arise, possibly because shoot nitrogen concentrations and C:N ratio were unaffected. To our knowledge, this is the first report of an insect ecosystem engineer alleviating the effects of predicted drought events on plants via physical manipulation of the soil matrix. Moreover, their effects did not change plant suitability to an above‐ground herbivore, pointing to potential beneficial role for insect ecosystem engineers in climate change adaptation and crop protection. Abstract : Lay Summary